Carvacrol Alleviates Hyperuricemia-Induced Oxidative Stress and Inflammation by Modulating the NLRP3/NF-κB Pathwayt - Riaz M; Al Kury LT; Atzaz N; Alattar A; Alshaman R; Shah FA; Li S (Dove Medical Press, 2022)
Muhammad Riaz,1 Lina Tariq Al Kury,2 Noreen Atzaz,3 Abdullah Alattar,4 Reem Alshaman,4 Fawad ali Shah,1 Shupeng Li5 1Riphah Institute of Pharmaceutical Sciences, Riphah International University, Islamabad, Pakistan; 2Department of Natural and Health Sciences Zayed University, Abu Dhabi, United Arab Emirates; 3Department of Pathology, Benazir Bhutto Hospital, Rawalpindi, Pakistan; 4Department of Pharmacology and Toxicology, Faculty of Pharmacy, University of Tabuk, Tabuk, Kingdom of Saudi Arabia; 5State Key Laboratory of Oncogenomics, School of Chemical Biology and Biotechnology, Peking University Shenzhen, Shenzhen, People's Republic of ChinaCorrespondence: Fawad ali Shah; Shupeng Li, Email fawad.shah@riphah.edu.pk; lisp@pkusz.edu.cnPurpose: Gouty arthritis is generally induced by the accumulation of monosodium urate (MSU) crystals in the joints due to elevated serum uric acid levels, potentially leading to serious pathological disorders such as nephrolithiasis, renal failure, and acute gouty arthritis. In this study, we aimed to validate the anti-gout effects of carvacrol, a phenolic monoterpene.Materials and Methods: Male Sprague-Dawley rats were divided into normal saline, disease group by injecting potassium mono-oxonate (PO) at a dose of 250 mg/kg, and three treatment groups, either with carvacrol 20 mg/kg or 50 mg/kg and 10 mg/kg allopurinol. The blood and tissue samples were subsequently collected and analyzed using different biochemical and histopathological techniques.Results: Our results revealed a significant increase in the serum levels of oxidative stress-related markers, namely, uric acid and C-reactive protein (CRP), and NLRP3 inflammasome-dependent inflammatory mediators, including nuclear factor kappa B (NF-κB) and tumor necrosis factor-alpha (TNF-α). Carvacrol administration for seven consecutive days exhibited significant anti-hyperuricemic and anti-inflammatory effects in a dose-dependent manner. Notably, the 50 mg/kg carvacrol treatment was observed to produce results similar to the allopurinol treatment. Furthermore, the renal safety of carvacrol was confirmed by the renal function test.Conclusion: Carvacrol potentially alleviates hyperuricemia-induced oxidative stress and inflammation by regulating the ROS/NRLP3/NF-κB pathway, thereby exerting protective effects against joint degeneration.Keywords: hyperuricemia, gout, inflammation, NLRP3, monosodium urate crystals